2021
DOI: 10.1016/j.phymed.2020.153317
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phytochemicals as potential therapeutic agents that binds to Nsp15 protein target of coronavirus (SARS-CoV-2) that are capable of inhibiting virus replication

Abstract: Highlights Sarsasapogenin, ursonic acid, ajmalicine, novobiocin, silymarin and aranotin are strongly binding to Nsp15 target using autodock software. Curcumin, piperine, gingerol, rosmarinic acid, ursolic acid and alpha terpinyl acetate show strong molecular interaction using swissdock software. Most of the phytochemicals predicted to have an ideal pharmacokinetic profile using druolito software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 21 publications
0
64
0
3
Order By: Relevance
“…The study reported that ajmalicine, alpha terpinyl acetate, curcumin, gingerol, novobiocin, piperine, rosmarinic acid, silymarin, and aranotin, sarsasapogenin, and ursonic acid exhibited binding with the Nsp15 protein. Therefore, these phytochemicals might effectively inhibit viral replication and their efficacy should be evaluated in pre-clinical as well as clinical studies [ 182 ]. Another study conducted molecular docking simulations between functional foods and SARS-CoV-2 Mpro.…”
Section: Available Repurposed Drugs Against Covid-19mentioning
confidence: 99%
“…The study reported that ajmalicine, alpha terpinyl acetate, curcumin, gingerol, novobiocin, piperine, rosmarinic acid, silymarin, and aranotin, sarsasapogenin, and ursonic acid exhibited binding with the Nsp15 protein. Therefore, these phytochemicals might effectively inhibit viral replication and their efficacy should be evaluated in pre-clinical as well as clinical studies [ 182 ]. Another study conducted molecular docking simulations between functional foods and SARS-CoV-2 Mpro.…”
Section: Available Repurposed Drugs Against Covid-19mentioning
confidence: 99%
“…Curcumin has already been demonstrated to inhibit SARS-CoV-1 replication (EC 50 of >10 µM), the coronavirus which caused the 2003 epidemic [66]. Additionally, several molecular docking studies have been performed that suggest curcumin would be effective at inhibiting SARS-CoV-2 replication [67], through interacting with the spike glycoprotein and inhibiting angiotensin-converting enzyme 2 (ACE2) [68], inhibiting the viral non-structural protein Nsp15 [69], or inhibiting the main viral protease [70].…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…There was an attempt to design a theoretical model of a carbon nanotube-UNA drug matrix to block the entry of human immunodeficiency virus (HIV) [86]. Moreover, a recent document demonstrated that UNA has the potential to strongly interact with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Nsp15, an endoribonuclease which is essential for the lifecycle of coronaviruses [87,88]. Molecular docking and dynamics analyses show that UNA is predicted to bind stably with the catalytic residues of SARS-CoV-2 Nsp15 via hydrogen bonds, suggesting that UNA may represent one of drug candidates to inhibit replication of SARS-CoV-2, the virus responsible for the coronavirus disease 2019 (COVID-19) pandemic.…”
Section: Antiviral Effectsmentioning
confidence: 99%